Characterization of bacteriocins produced by lactic acid bacteria from fermented beverages and optimization of starter cultures - Von Mollendorff, Johan Wilhelm (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Microbiology))--Stellenbosch University, 2008.